Determination of the Optimum Plot Size for Tomato Seedlings: An Advanced Research - Oliveira, Jeniffer Ribeiro De; Altoé, Jalille Amim; Oliosi, Gleison; Lima, Alex Silva; Rosa, Luã Víthor Chixaro Almeida Falcão; Gomes, Raquel da Silva; Tognere, Jasmyn; Salomão, Bruna Alves; Santos, Mayara Nascimento; Cavalcanti, André Cayô; Nascimento, Alan de Lima; Oliveira, Vinicius de Souza (Current Topics in Agricultural Sciences Vol. 2, 2021)
The objectives of this work were to determine the optimum plot size for tomato seedlings by Hatheway’s method, using the Mestiço and Ozone cultivars, and verify the possibility to obtain the optimum plot size only by nondestructive characteristics. Determining the optimal plot size based on scientific criteria is extremely important to give greater credibility to the experimental results. Non-destructives (aerial part height, stem diameter, number of leaves and leaf area) and destructives (aerial part dry matter, root dry matter, total dry matter and Dickson quality index) characteristics were evaluated. For each characteristic evaluated, experimental plans were simulated in a randomized block design with the combination of I treatments (I = 3, 4, 5, ..., 10, 15, 20 and 25) and R repetitions (R= 3, 4, 5, 6 and 7). The optimum plot size ranged according to the characteristic evaluated. Considering the number of treatments, repetitions and the same experimental accuracy, the stem diameter showed the highest size plot. Thus, the stem diameter can be used as a basis characteristic for the non-destructives characteristics, without the need to destroy the seedling.